2018
DOI: 10.1021/acs.cgd.8b00362
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil–Malonic Acid Cocrystal: Physicochemical Characterization, pH-Solubility, and Supersaturation Studies

Abstract: The purpose of this study was to enhance the solubility and dissolution of a poorly water-soluble drug, tadalafil (TDF), by cocrystal formation with malonic acid (MOA), to characterize the cocrystal structure and to quantify the cocrystal solution behavior. The crystal structure revealed a 1:1 stoichiometry, wherein the TDF molecules form a double layered structure through N–H···OC interactions linked to a catemeric chain of MOA molecules via O–H···O hydrogen bonds. Cocrystal solubility advantage (SA defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Indeed, rapid conversion of the cocrystals into pure drug was demonstrated by PXRD analysis of the solids recovered after the dissolution tests in short time periods (~1-5 min, Figure 3). A similar behavior has been documented for other cocrystal phases in the literature [24,25,30,36,37,[55][56][57]. For example, exemestane-maleic-acid cocrystals did not increase solubilization of the drug due to rapid phase transformation [55].…”
Section: Performance Of Ntz Cocrystals Under Non-sink Conditionssupporting
confidence: 77%
See 4 more Smart Citations
“…Indeed, rapid conversion of the cocrystals into pure drug was demonstrated by PXRD analysis of the solids recovered after the dissolution tests in short time periods (~1-5 min, Figure 3). A similar behavior has been documented for other cocrystal phases in the literature [24,25,30,36,37,[55][56][57]. For example, exemestane-maleic-acid cocrystals did not increase solubilization of the drug due to rapid phase transformation [55].…”
Section: Performance Of Ntz Cocrystals Under Non-sink Conditionssupporting
confidence: 77%
“…The use of excipients such as polymers and surfactants constitutes an efficient strategy to prolong drug supersaturation achieved from pharmaceutical cocrystals [23][24][25]36,57]. An addition of a cellulosic polymer into the dissolution medium for powder dissolution studies under non-sink conditions revealed that these can induce a supersaturation effect starting from NTZ-SUC and NTZ-GLU cocrystals.…”
Section: Performance Of Ntz Cocrystals Under Non-sink Conditionsmentioning
confidence: 99%
See 3 more Smart Citations